Notch signaling in descending thoracic aortic aneurysm and dissection. - Sili Zou; Pingping Ren; Mary Nguyen; Joseph S Coselli; Ying H Shen; Scott A LeMaire (PLoS ONE, 2012)
BACKGROUND:Descending thoracic aortic aneurysm and dissection (DTAAD) is characterized by progressive medial degeneration, which may result from excessive tissue destruction and insufficient repair. Resistance to tissue destruction and aortic self-repair are critical in preventing medial degeneration. The signaling pathways that control these processes in DTAAD are poorly understood. Because Notch signaling is a critical pathway for cell survival, proliferation, and tissue repair, we examined its activation in DTAAD. METHODS:We studied descending thoracic aortic tissue from patients with sporadic thoracic aortic aneurysm (TAA; n = 14) or chronic thoracic aortic dissection (TAD; n = 16) and from age-matched organ donors (n = 12). Using western blot, real-time RT-PCR, and immunofluorescence staining, we examined aortic tissue samples for the Notch ligands Delta-like 1, Delta-like 4 (DLL1/4), and Jagged1; the Notch receptor 1 (Notch1); the Notch1 intracellular domain (NICD); and Hes1, a downstream target of Notch signaling. RESULTS:Western blots and RT-PCR showed higher levels of the Notch1 protein and mRNA and the NICD and Hes1 proteins in both TAA and TAD tissues than in control tissue. However, immunofluorescence staining showed a complex pattern of Notch signaling in the diseased tissue. The ligand DLL1/4 and Notch1 were significantly decreased and NICD and Hes1 were rarely detected in medial vascular smooth muscle cells (VSMCs) in both TAA and TAD tissues, indicating downregulation of Notch signaling in aortic VSMCs. Interestingly Jagged1, NICD, and Hes1 were highly present in CD34+ stem cells and Stro-1+ stem cells in aortas from TAA and TAD patients. NICD and Hes1 were also detected in most fibroblasts and macrophages that accumulated in the aortic wall of DTAAD patients. CONCLUSIONS:Notch signaling exhibits a complex pattern in DTAAD. The Notch pathway is impaired in medial VSMCs but activated in stem cells, fibroblasts, and macrophages.